TERRITORIAL DIFFERENTIATION OF KRYVBAS OLDEN DUMPS VEGETATION COVER (Ecological Bulletin of Kryvyi Rih District, 2023)
Old age dumps have significant scientific value in terms ofpreserving information about the course of the late stages of successional development of vegetation and mining landscapes in general. The study of the spatial distribution of vegetation on the iron ore dumps of the KryvyiRih Iron Ore Basin is currently fragmentary, so information on the territorial and structural aspect of the vegetation cover organization such objects ofindustrial heritage is the next step in learning the ways of their genesis. The aim of the work is to identify the patterns of territorial differentiation of iron ore dumps vegetation in Kryvyi Rih Iron Ore Basin using the examples of small dumps in the gully Pivnichna Chervona and the olden mines “Dubova balka” and “Rakhmanivskyi”. The work is based on the materials of field research conducted in 2016–2021; 80 geobotanical descriptions were usedand 5 large-scale vegetation maps were created. The results of the territorial differentiation research of phytostructures, it was established that it is causedby the heterogeneity of ecotopes and is characterized by a fine-contour mosaic. Over a hundred-year period of self-development of these post-mining landscapes, ruderal cenostructures were completely eliminated from thevegetation, instead, “quasi-steppe” and petrophytic communities, similar to natural ones in terms of floral composition, were formed. The share of woodyvegetation is higher in the territorial dumps structure in the north of the region, compared to the dumps in the central part; at the same time, in the northern part of Kryvyi Rih there is a predominance of representatives of the aboriginal flora in the cenostructures. The presence of drought-resistant adventitious species in the woody vegetation increases as the dumps move south along thelatitudinal gradient and the contours of the vegetation themselves shift from the plateau to the slopes with more favourable microclimatic conditions. The regularity of territorial differentiation is the presence of significant areas of ecotopes without vegetation on the steep slopes of all the investigated dumps.We associate the further stage of their overgrowth with the development of tree-shrub communities. Prospects for further research are to use them in the organization of the ecological monitoring system of technogenesis zones of the Kryvyi Rih region.
Keywords: dumps; mosaic; coenostructures; herbal and treeshrub vegetation